(untitled) (Research, Society and Development, 2025)
Objective: To understand the epidemiological profile of reports of self-harm, commonly called suicide attempts, in the metropolitan region of Maringá between 2012 and 2022. Methods: This quantitative and descriptive research used data from the National System of Injuries and Notification (SINAN). It was decided to remove children under 5 years of age and Ign/white to structure the epidemiological information. Results: A total of 7,898 cases of self-harm were reported. Young adults of the white sex, female, between 20 and 29 years old, with complete high school education are the most affected. Regarding the most used means to cause self-harm, poisoning obtained 5,607 reports, followed by 1,167 records for sharp objects. The evolution of these cases cannot be assessed due to the lack of registration in the system. Regarding geographic distribution, among the 26 municipalities analyzed, Maringá had the highest record of 55.93% of suicide attempts. Conclusions: It is concluded that the findings of this research are in line with other national studies corroborating that self-harm is a public health problem, as it highlights the increasing number of suicide attempts. The results indicate the importance of reflecting on strategies and actions in mental health. It is emphasized that self-harm can be avoided through promotion and prevention actions at all levels of health care, avoiding the fatal outcome, suicide. The importance of training primary care health teams to screen, manage and refer suspected cases early is highlighted.